(untitled) (Journal of Contemporary Philology, 2022)
In this research, we examine how participants in online forum discussions express commitment to the views they express. Discussions on COVID-19 on two Macedonian fora, Kajgana and Femina, are analyzed. The research is based on sociolinguistically oriented interpretations of stance (Du Bois 2007, Barton and Lee 2013) and on the Appraisal Framework (Martin and White 2005, Oteíza 2017), both promoting the dialogic perspective. The concept of stancetaking refers to how people position themselves in relation to what is said, other people and objects discussed and in relation to their interlocutors (Barton and Lee 2013:87). We focus on the linguistic, rhetorical and discourse-pragmatic strategies employed by the authors to express their attitude, conviction and degree of commitment to what is being talked about in the interaction sequences excerpted from the discussions.